Assessment of the cytotoxic effect and in vitro evaluation of the anti-enteroviral activities of plants rich in flavonoids - Nabil Ben Salem Abid, Zyed Rouis, Mohamed Ali Lassoued, Souad Sfar, Mahjoub Aouni (Journal of Applied Pharmaceutical Science)
Nanoparticles derived from plants known for their high content of flavonoids provide a biologically inspired route to designing therapeutic agents and a means of reducing nanoparticle toxicity. Little is currently known on the antiviral activity of Salvia officinalis L. and Washingtonia filifera H.Wendl aqueous extracts and their corresponding nanoparticles. In the present study, antiviral activity of subset extracts obtained from aerial parts of Salvia officinalis L. and Washingtonia filifera H.Wendl and nanoparticles derived from these plants were investigated against coxsackievirus B3 (CVB3). Different concentrations of extracts (7.8, 15.6, 31.25, 62.5, 125, 250, 500, and 1000 µg/mL) were tested for their cytotoxic effect and the antiviral activity was carried out using three non cytotoxic concentrations against CVB3 in Vero cells. The cell viability was carried out using tetrazolium dye (MTT). The experiment was carried out by incubating the extracts with either virus or cells prior to infection. The silver nanoparticles derived from the tested plant extracts enhance antiviral activity at non cytotoxic concentrations. The biosynthesized nanoparticles may be further characterized to better evaluate their antiviral potential against other viral pathogens.
Keywords: Antiviral activity, Enterovirus, Nanoparticles, Salvia officinalis, Washingtonia filifera.